(untitled) (Ictus, 2022)
Introduction: Lateral medullary syndrome (LMS) is the most common of the crossed brainstem syndromes involving the posterior circulation. There are several patterns of sensory dysfunction according to the site of lesion. Although some sources still cite cardioembolism or atherothrombosis as the main causes of lateral medullary infarctions, it is increasingly recognized vertebral artery dissection (VAD) as the chief etiology. Methods: We report on nine patients presenting with LMS due to confirmed VAD in predominantly young individuals (6 men, age range 23-54 years). Results: Most patients presented with sudden headache or neck pain, ataxia and nystagmus (n=7). On neurological examination the majority (n=7) had crossed sensory loss of the classical Wallenberg pattern and all but two had Horner syndrome. At 6-month follow-up no deaths or recurrences were observed: five patients were completely asymptomatic, three patients persisted with mild or moderate deficits and one was unable to walk without assistance. Seven patients had dysphagia that evolved unevenly within the 6-month follow-up period. We also discuss on the clinical and neuroanatomical correlates behind the LMS variants. Conclusions: VAD should be suspected in patients presenting with LMS and headache or neck pain. Given the intricacy of the medulla anatomy and the serendipitous nature of ischemia after VAD, a missing sign from the original Wallenberg’s description is not incompatible with a lateral medullary infarction.